Analisis Butir Soal Ulangan Umum Mata Pelajaran Fiqih Madrasah Ibtidaiyah Kelas IV (Studi Kasus di Madrasah Ibtidaiyah Wahid Hasyim) - Adhi Setiyawan (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2009)
Teachers used tests to measure the competence and effectiveness of instructional programs. Test must be tested in quality empirically. The item still must be tested by trial, and the result of this test obtained evidence about the quality of item test. By doing the examination hence a test can be applied in evaluation. Repairs, omission or things required in evaluating. At this article brief analysis toulangan umum fiqih at Madrasah Ibtidaiyah class IV. With examinee 20 students. Test analysis applies program ITEMAN version 3.00. ITEMAN represents of the classical Test Theory. Based on analysis item, the test need to revise. The test middle difficulty because mean P is 0.570